The specific contributions of activities to household electricity demand - Grunewald, P; Diakonova, M (Elsevier, 2019)
In this paper we present new methods to collect and analyse household activity and electricity consumption data. We show how such data can be used to establish relationships between activities and electricity consumption in two different ways. First we create direct associations between activities and the electricity demand at the time. This electricity footprint gives an insight into the typical load intensity of an activity, which can include other activities that are commonly performed in close temporal proximity. Our novel contribution is the concept of marginal electricity demand which can be attributed to specific activities. To disaggregate and approximate the loads for such an activity, we present a new regression approach. The marginal demand of an activity is based on its relative load contribution to any other activity within a collection of over 18,000 activity pairs. Meal types stand out as clearly distinguishable activities. Hot meal related activities show some of the strongest positive contributions to demand, whereas cold meals tend to reduce demand at the time of reporting. Activities such as a hot drink can lead to an overall reduction in demand at the time, despite their direct energy consumption. The potential of this marginal metric will be discussed as a new way to understand energy service demands. Unlike conventional attribution of demand to appliances, it is possible for activities to have a negative marginal demand. This opens up new opportunities to conceptualise the meaning of energy service demand and approaches to encourage demand reduction or shifting through positive actions.